2008
DOI: 10.1111/j.1399-6576.2008.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled comparison between single doses of intravenous and intramuscular morphine with respect to analgesic effects and patient safety

Abstract: A 10 mg bolus dose of IV morphine given to patients with moderate pain after surgery does not cause severe respiratory depression, but provides more rapid and better initial analgesia than 10 mg given IM. IV morphine even at a dose as high as 10 mg IV is well tolerated if there is a certain level of pain at its administration. The safety of IV morphine on the general ward needs to be further explored in adequately controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…This is consistent with the rapid onset of pain relief reported by Johnston et al in their study of pre-hospital analgesia for visceral pain, which found a mean reduction in visual/verbal analog scale pain score (0–10 scale) with methoxyflurane of 2.0 (95% CI: 1.7, 2.2) after 5 min and 2.5 (95% CI: 2.1–2.9) on arrival at hospital, compared with 1.6 (95% CI: 1.4, 1.8) and 3.2 (95% CI: 2.9, 3.5), respectively, for intranasal fentanyl [19]. The onset of pain relief with methoxyflurane is also similar to that reported by Tveita et al for a 10 mg bolus dose of IV morphine [32]. Although methoxyflurane is currently only licensed for emergency relief of pain due to trauma in Europe, several studies in Australia and New Zealand have also demonstrated its effectiveness as a procedural analgesic [21, 3336].…”
Section: Discussionsupporting
confidence: 71%
“…This is consistent with the rapid onset of pain relief reported by Johnston et al in their study of pre-hospital analgesia for visceral pain, which found a mean reduction in visual/verbal analog scale pain score (0–10 scale) with methoxyflurane of 2.0 (95% CI: 1.7, 2.2) after 5 min and 2.5 (95% CI: 2.1–2.9) on arrival at hospital, compared with 1.6 (95% CI: 1.4, 1.8) and 3.2 (95% CI: 2.9, 3.5), respectively, for intranasal fentanyl [19]. The onset of pain relief with methoxyflurane is also similar to that reported by Tveita et al for a 10 mg bolus dose of IV morphine [32]. Although methoxyflurane is currently only licensed for emergency relief of pain due to trauma in Europe, several studies in Australia and New Zealand have also demonstrated its effectiveness as a procedural analgesic [21, 3336].…”
Section: Discussionsupporting
confidence: 71%
“…In addition, the median time to first pain relief for the methoxyflurane group was 4 min. This compares favourably with a median time to onset of meaningful pain relief of 11 min with intranasal fentanyl (IF),19 16 min with oromucosal fentanyl,19 and 5 min with intravenous morphine sulfate 20. There was a higher occurrence of AEs in methoxyflurane-treated patients than in those treated with placebo; however, in general, methoxyflurane was well tolerated, with the majority of adverse reactions being mild, transient and in line with anticipated pharmacological action.…”
Section: Discussionmentioning
confidence: 94%
“…Emphasis was placed on intravenous and intranasal methods of administration given their shorter onset of action as opposed to intramuscular and oral analgesia. 28 Pain reduction and the prevalence of serious adverse events (SAEs), including hypotension, hypoventilation, allergy, hypoxia, and/or altered level of consciousness, were considered important outcomes. The panel considered minor adverse events (AEs), such as nausea, dizziness, bad taste, and pruritus, as outcomes of lesser importance.…”
Section: What Is the Basis Of Suggesting Morphine And Fentanyl For Pamentioning
confidence: 99%
“…28,[31][32][33]35 There were few direct comparisons made between IV morphine and IV fentanyl, although a number of studies compared IN fentanyl with IM or IV morphine. [29][30][31][32]36 Intravenous administration was the most commonly researched route for fentanyl, but in a few observational studies, intranasal delivery appeared to be safe, effective, and less painful than intravenous cannulation.…”
Section: Routesmentioning
confidence: 99%